2018
DOI: 10.1371/journal.pone.0191389
|View full text |Cite
|
Sign up to set email alerts
|

Preconception use of cART by HIV-positive pregnant women increases the risk of infants being born small for gestational age

Abstract: BackgroundThe benefits of combination anti-retroviral therapy (cART) in HIV-positive pregnant women (improved maternal health and prevention of mother to child transmission [pMTCT]) currently outweigh the adverse effects due to cART. As the variety of cART increases, however, the question arises as to which type of cART is safest for pregnant women and women of childbearing age. We studied the effect of timing and exposure to different classes of cART on adverse birth outcomes in a large HIV cohort in the Neth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 31 publications
(42 reference statements)
1
53
2
2
Order By: Relevance
“…Despite the high proportion of SGA born fetuses in this study and the presence of PI categorized ART, there was no statistical difference. These data differ from findings of a study that identified a higher risk for restricted fetal growth in pregnant women using regimens based on PI initiated before gestation [13], and from a study conducted by Van der Merwe et al 2011that showed an association between SGA birthweight and the use of PI regimens [42].…”
Section: Plos Onecontrasting
confidence: 93%
See 1 more Smart Citation
“…Despite the high proportion of SGA born fetuses in this study and the presence of PI categorized ART, there was no statistical difference. These data differ from findings of a study that identified a higher risk for restricted fetal growth in pregnant women using regimens based on PI initiated before gestation [13], and from a study conducted by Van der Merwe et al 2011that showed an association between SGA birthweight and the use of PI regimens [42].…”
Section: Plos Onecontrasting
confidence: 93%
“…However, a common difficulty in previous studies is the need to control outcomes not only for comorbidities that affect growth and are prevalent in general gestations and in HIV-infection status (hypertensive disorders, smoking, diabetes, illicit drugs, fetal malformation, congenital syphilis and maternal body mass index (BMI) disorders) but also for the use of highly active antiretroviral therapy (HAART) [9,10]. In the literature related to adverse perinatal outcomes, conflicting data have been presented regarding the occurrence of restricted growth and preterm births in pregnant women infected with HIV under antiretroviral schemes with and without protease inhibitors (PI) before and after conception [10][11][12][13][14]. In this context, and considering the evidence that the postnatal growth of the children of HIV-infected women is often delayed or fails to meet expected values even without the occurrence of vertical transmission (VT) of the virus [15],new studies about fetal and placental growth in HIV-infected pregnant women are justified.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the SGA rate, HIV infection itself and ART both contributed to a higher SGA rate [11,19]. Among the ART regimens, one mouse-based model revealed that PI will affect the IUFG by decreasing the progesterone level, which leads to fetal growth restriction [14].…”
Section: Discussionmentioning
confidence: 99%
“…Small-for-gestational age (SGA), preterm birth (PTB), or low birth weight (LBW) in HIV-positive women is widely observed in several cohort studies [7][8][9][10][11][12]. The possible risk factors for SGA include Hepatitis B infection and ART initiation later than 14 weeks gestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation